The Pedagogical Potential of the Integrative Project as a Classroom Strategy: A Case Study in the Industrial Technology Program at the Universidad de Santander (UDES) - Galeano Barrera, Claudia Jazmin; Zamudio Peña, William Humberto; Duro Novoa, Viviana; Martínez Quintero, Ana Francisca (Ingeniería Solidaria, 2017)
Introduction: This article summarizes the classroom experiences obtained in the application of “The integrative project as a classroom strategy in Industrial Technology courses”, carried out in the fourth semester of the technological program in 2013 and 2014, at the Universidad de Santander (UDES). The objective of this work, carried out during 2015, is to show that the appropriation and integration of the students’ knowledge is materialized in prototype innovation products and in dissertations focused on entrepreneurship.Method: In the course of the integrative project, the formative project methodology was used for building the student’s basic, professional and research skills. The pedagogical experience provides students with the opportunity to participate by proposing innovative ideas as a response to the context problem, as well as by taking advantage of the acquired knowledge and the use of university resources.Results: Appropriation of the integrative project by the student stimulates his creativity to produce the prototype of his proposal. The set of prototypes is donated to a rural community in Bucaramanga, which strengthens the research-outreach alliance, including the preparation of dissertations.Conclusions: The strengthening of skills oriented to the know-how allows the student to be trained comprehensively, feeds him with knowledge, allows him to use it (praxis), and positions him in the market with entrepreneurial ability.
Keywords: learning; educator; entrepreneurship; innovation; integrative project